2023
DOI: 10.1039/d2bm02014a
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of precision nanofiber micelleplexes for DNA delivery

Abstract: As nucleic acid (NA) technologies continue to revolutionize medicine, new delivery vehicles are needed to effectively transport NA cargoes into cells. Uniform and length-tunable nanofiber micelleplexes have recently shown promise...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 84 publications
0
6
0
Order By: Relevance
“…Next, we investigated if codelivery of antibiotics with nanofibers could provide synergistic enhancement of antibacterial activity, while also providing further insights into the mechanism of action. , To this end, the dye-free BCP PFTMC 26 - b -PDMAEMA 424 was synthesized, and nonfluorescent nanofibers were prepared via living CDSA (see Supporting Information for full details) . The newly composed nanofibers were of comparable length ( L n = 109 nm, D̵ L = 1.07, core height = 7 nm, core width = 10–13 nm, Figures , S24a, and Table S3) to the shorter nanofibers used for investigating the mechanism of action microscopically ( L n = 104 nm).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Next, we investigated if codelivery of antibiotics with nanofibers could provide synergistic enhancement of antibacterial activity, while also providing further insights into the mechanism of action. , To this end, the dye-free BCP PFTMC 26 - b -PDMAEMA 424 was synthesized, and nonfluorescent nanofibers were prepared via living CDSA (see Supporting Information for full details) . The newly composed nanofibers were of comparable length ( L n = 109 nm, D̵ L = 1.07, core height = 7 nm, core width = 10–13 nm, Figures , S24a, and Table S3) to the shorter nanofibers used for investigating the mechanism of action microscopically ( L n = 104 nm).…”
Section: Resultsmentioning
confidence: 99%
“…The EC 50 (half maximal effective concentration) of PFTMC- b -PDMAEMA materials has been previously measured against a variety of mammalian cell-types and ranges from 12 to 20 μg/mL . No cytotoxicity was observed for PFTMC 26 - b -PDMAEMA 424 against U-87 MG glioblastoma cells at 6.25 μg/mL E.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Polycationic vectors mainly refer to polymers with positively charged groups, which rely on electrostatic interaction to complex nucleic acids. [33][34][35] Conventional polycationic vectors such as poly (2-N,N-dimethylaminoethylmethacrylate) (PDMAEMA) [36][37][38] and polyethyleneimine (PEI) 31,[39][40][41] have already been proven to have outstanding complexation capability due to their high positive charge density, while unignorable cytotoxicity, protein absorption behavior, and high hemolysis rate caused by the positive charges compromise their transfection efficiency and bio-compatibility. As a strategy to overcome these shortcomings, the fabrication of hydroxyl-rich polycationic vectors is suggested.…”
Section: Zichen Humentioning
confidence: 99%
“…A means to overcoming this drawback was reported by Manners and co-workers who demonstrated that the inclusion of a short hydrophobic block in the polymer architecture results in the formation of an amorphous domain capable of encapsulating drugs at the core−corona interface. 21 In general, studies of crystalline-core polymer nanoparticles have shown them capable of functioning as MRI contrast agents, 22 drug/gene delivery vehicles, 18,21,23,24 antimicrobials, 25,26 and penetrating tumor spheroids, 9 further emphasizing their potential utility. Recently, our group reported the heat-induced living CDSA of poly(2-oxazoline) (POx) block copolymers in water.…”
mentioning
confidence: 99%